Procalcitonin and C-reactive protein - early predictors of low colorectal anastomotic leakage - Yu. A. Shelygin; M. A. Tarasov; M. A. Sukhina; I. V. Zarodnyuk; Ye. G. Rybakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To determine diagnostic value of procalcitonin (PCT) and C-reactive protein (CRP) at anastomotic leakage (AL) following lower anterior resection (LAR) of the rectum. Material and methods. Overall 100 patients underwent surgery for epithelial tumors of rectum in the period 2013-2016 yy in the volume of LAR with the formation of anastomosis and preventive stoma. In patients without clinical symptoms radiopaque study was performed in order to identify asymptomatic AL on day 7 after the surgery. AL rate, difference in PCT and CRP levels in patients with AL and consistent anastomosis were assessed along with sensitivity, specificity, positive and negative predictive value of these markers. Results. AL was diagnosed in 20% (20 of 100) of patients: in 11% (11 of 100) - with clinical manifestations, in 9% (9 of 100) - without clinical symptoms (contrast leakage according to X-ray study). In the group of patients with anastomotic leak, the median of C-reactive protein level differed from that in patients with uncompromised integrity of anastomosis at 3rd day after surgery (156 mg/L vs 81 mg/L, respectively - t-test, p=0.0004) and postoperative day 6 (136 mg/L vs. 52 mg/L, respectively - t-test, p